(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Gene editing represents one of the most transformative biotechnologies of the 21st century, offering unprecedented precision in modifying DNA to treat genetic diseases, enhance agricultural productivity, and potentially alter the trajectory of human evolution. This narrative article explores the revolutionary CRISPR-Cas9 technology, its clinical applications including the landmark FDA approval of Casgevy for sickle cell disease, emerging ethical frameworks, and the regulatory landscape shaping this rapidly evolving field. With the global gene editing market projected to reach 45 billion by 2035 , understanding this technology’s capabilities, limitations, and societal implications has never been more critical.